Factors Associated with Work-Related Fatigue and Recovery in Hospital Nurses Working 12-Hour Shifts. (October 2014) - Han, Kihye; Trinkoff, Alison M.; Geiger-Brown, Jeanne
Nurse fatigue threatens both nurse and patient safety; fatigue affects nurses' neurocognitive functioning and hinders their work performance. The authors assessed the association of work and non-work factors with acute and chronic fatigue and intershift recovery among hospital nurses working 12-hour shifts. This study used survey data from 80 nurses who provided full-time direct patient care on medical-surgical and critical care units in a large teaching hospital. Psychological job demands (e.g., work load and social support from supervisor or coworker) were significantly associated with acute and chronic fatigue and intershift recovery. Rotating shifts were significantly related to acute fatigue. Findings suggest the need for a comprehensive approach to fatigue management, including organizational support to provide healthful work schedules and favorable nursing work environments, fewer psychological and physical demands, and assistance to improve nurses' sleep quality and quantity.